Intensification of Processes for the Production of Ethyl Levulinate Using AlCl3·6H2O - Carlo Pastore; Valeria D’Ambrosio (Energies, 2021)
A process for obtaining ethyl levulinate through the direct esterification of levulinic acid and ethanol using AlCl3·6H2O as a catalyst was investigated. AlCl3·6H2O was very active in promoting the reaction and, the correspondent kinetic and thermodynamic data were determined. The reaction followed a homogeneous second-order reversible reaction model: in the temperature range of 318–348 K, Ea was 56.3 kJ·K−1·mol−1, whereas Keq was in the field 2.37–3.31. The activity of AlCl3·6H2O was comparable to that of conventional mineral acids. Besides, AlCl3·6H2O also induced a separation of phases in which ethyl levulinate resulted mainly (>98 wt%) dissolved into the organic upper layer, well separated by most of the co-formed water, which decanted in the bottom. The catalyst resulted wholly dissolved into the aqueous phase (>95 wt%), allowing at the end of a reaction cycle, complete recovery, and possible reuse for several runs. With the increase of the AlCl3·6H2O content (from 1 to 5 mol%), the reaction proceeded fast, and the phases’ separation improved. Such a behavior eventually results in an intensification of processes of reaction and separation of products and catalyst in a single step. The use of AlCl3·6H2O leads to a significant reduction of energy consumed for the final achievement of ethyl levulinate, and a simplification of line-processes can be achieved.